Incubation temperature induced developmental plasticity of cold responsive physiological phenotypes in Japanese Quails - Yingxin Kou; Rongmiao Zhang; Xiaoqian Li; Na Zhu; Yihang Huang; Shuping Zhang (Avian Research)
Embryonic development is a critical period for phenotype formation. Environmental variation during embryonic development can induce changes in postnatal phenotypes of animals. The thyroxine secretion and aerobic metabolic activity of small birds are important phenotypes closely related to their winter survival. In the context of climate change, it is necessary to determine whether temperature variation during incubation in birds leads to developmental plasticity of these cold responsive phenotypes. We incubated Japanese Quail (Coturnix japonica) eggs at 36.8 °C, 37.8 °C, and 38.8 °C, and raised the chicks to 35-day old at 22 °C with same raising conditions, then all the quails were exposed to gradually temperature dropping environment (from 15 °C to 0 °C). After cold treatment, serum T3 level, resting metabolic rate, skeletal muscle and liver metabolomes of the birds were measured. The serum T3 levels were significantly lower in the 38.8 °C group and significantly higher in the 36.8 °C group compared to the 37.8 °C group. The metabolic rate in the 38.8 °C group was significantly lower compared to the 37.8 °C group. Compared with the 37.8 °C group, metabolites involved in the tricarboxylic acid cycle in the liver were significantly lower in the 38.8 °C group, and metabolites related to lipid oxidation metabolism and fatty acid biosynthesis were significantly lower in the skeletal muscles in the 38.8 °C group but significantly higher in the 36.8 °C group. These results indicate that incubation temperature variation can lead to developmental plasticity in cold responsive physiological phenotypes. Higher incubation temperature may impair the capacity of birds coping with cold challenge.